2007
DOI: 10.1016/j.neuron.2007.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Sept4, a Component of Presynaptic Scaffold and Lewy Bodies, Is Required for the Suppression of α-Synuclein Neurotoxicity

Abstract: In Parkinson disease (PD), alpha-synuclein aggregates called Lewy bodies often involve and sequester Septin4 (Sept4), a polymerizing scaffold protein. However, the pathophysiological significance of this phenomenon is unclear. Here, we show the physiological association of Sept4 with alpha-synuclein, the dopamine transporter, and other presynaptic proteins in dopaminergic neurons; mice lacking Sept4 exhibit diminished dopaminergic neurotransmission due to scarcity of these presynaptic proteins. These data demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
156
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(165 citation statements)
references
References 43 publications
5
156
0
3
Order By: Relevance
“…It has been reported that a septin 4 null mouse has a phenotype, including male infertility and anatomical abnormalities of the cerebellum (13,66). However, the knock-out septin 3, septin 5, or septin 6 mice showed no apparent effect on brain phenotype (7,66,67), indicating that there is developmental compensation and/or functional redundancy of various septins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that a septin 4 null mouse has a phenotype, including male infertility and anatomical abnormalities of the cerebellum (13,66). However, the knock-out septin 3, septin 5, or septin 6 mice showed no apparent effect on brain phenotype (7,66,67), indicating that there is developmental compensation and/or functional redundancy of various septins.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse anti-septin 7 ascites fluid was a gift from Dr. Randall Walikonis (University of Connecticut) (20). The guinea pig anti-rat ␥2 (to amino acids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] antibody was raised in our laboratory and affinity-purified on immobilized peptide. The specificity of the guinea pig anti-rat ␥2 antibody has been determined previously (21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Methodsmentioning
confidence: 99%
“…-/-mice had defects in behavior and reproduction, while SEPT5 -/-animals had elevated platelet hypersensitivity [25][26][27] . Septins have been reported to be perturbed in various human diseases, including neurological disorders, infection, and neoplasia [28] .…”
Section: Sept4mentioning
confidence: 99%
“…Electrophysiological study in -synuclein knockout mice revealed that -synuclein could act as an activitynegative regulator of DA neurotransmission at synaptic terminals (Abeliovich et al 2000). -synuclein is also speculated to have various other functions, such as modulation of tyrosine hydroxylase (TH) activation (Perez et al 2002), inhibition of vesicular monoamine transporter-2 (VMAT2) activity , and interaction with septin4, which have been implicated in exocytosis (Ihara et al 2007). Recently, Cooper and colleagues reported that -synuclein blocked endoplasmic reticulum (ER)-to-Golgi vesicular trafficking, and induced ER stress followed by cell death (Cooper et al 2006).…”
Section: α-Synucleinmentioning
confidence: 99%